The Influence of a Positive Empathetic Interaction on Conditioned Pain Modulation and Manipulation-induced Analgesia in People With Lateral Epicondylalgia. Issue 6 (June 2020) - Muhsen, Ahmad; Moss, Penny; Gibson, William; Walker, Bruce; Jacques, Angela; Schug, Stephan; Wright, Anthony
Abstract : Objective: Conditioned pain modulation (CPM) and manipulation-induced analgesia (MIA) are 2 forms of endogenous analgesia. Many forms of analgesia can be influenced by the nature of the patient-clinician interaction. The aim of this study was to evaluate the influence of an empathetic and supportive interaction on CPM and MIA in people with lateral epicondylalgia (LE). Material and Methods: In a double-blind, randomized, controlled trial, 68 participants with LE were assigned to 2 groups: the empathetic and neutral interaction groups. The interactions were carried out by a trained, professional role-play actor, playing the part of a research assistant. The research assistant actor spent 15 minutes before CPM and MIA assessment interacting with the participants in an empathetic or neutral manner. Immediately after the interaction, a blinded assessor measured pressure pain threshold at the symptomatic elbow and ipsilateral wrist during CPM and MIA testing. Linear mixed models were used to evaluate differences in CPM and MIA responses between the interaction groups. Results: There was a significant difference in Consultation and Relational Empathy scores between the groups ( P <0.001), indicating that the intervention group experienced a more empathic interaction. Both groups showed a significant increase in pressure pain threshold measures, indicative of a CPM and MIA analgesic response ( P <0.001), however, the analgesic responses were greater in the group that had experienced a supportive, empathetic interaction (post CPM, wrist: P <0.001; elbow: P =0.001) (post MIA wrist: P <0.001; elbow: P =0.001). Discussion: A single session of empathetic interaction positively influenced both CPM and MIA responses in people with LE.